THE KWL (KNOW, WANT TO KNOW, LEARN) STRATEGY IN ENHANCING THE READING COMPREHENSION OF DESCRIPTIVE TEXT AT THE SEVENTH GRADE STUDENTS OF SMPN 4 TARAKAN - Astiar, Astiar; Ulfaika, Romlah (Universitas Borneo Tarakan, 2024)
Reading comprehension is one of the basic skills in English that is quite difficult to master especially for students. Therefore, in teaching reading comprehension, an interesting teaching strategy such as KWL strategy is needed. The purpose of this study is to find out the significant effect of KWL strategy implementation on descriptive reading comprehension of junior high school 7th grade students. The research method used was pre-experiment method. The population of this study were seventh grade students of SMP Negeri 4 Tarakan with a sample of class VII-10 as many as 29 students. The research instruments used were multiple choice and true-false tests in the form of pre-test and post-test. In addition, the results of the data analysis obtained were processed using the SPSS version 25.0 program. The results of data analysis showed that the average pre-test result was 57.44 and the average post-test score was 78.89. The Shapiro Wilk Test result of 0.965 is higher than 0.05, which means that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Thus, it can be concluded that teaching descriptive text using KWL strategy is proven effective in improving reading comprehension of grade 7 students of SMP Negeri 4 Tarakan.Keywords: KWL Strategy, Reading Comprehension, Descriptive Text